TransArea : a literary history of globalization - Ette, Ottmar (De Gruyter, 2016)
"Ottmar Ette's TransArea proceeds from the thesis that globalization is not a recent phenomenon, but rather, a process of long duration that may be divided into four main phases of accelerated globalization. These phases connect our present, across the world's widely divergent modern eras, to the period of early modern history. Ette demonstrates how the literatures of the world make possible a tangible perception of that which constitutes Life, both of our planet and on our planet, which may only be understood through the application of multiple logics. There is no substitute for the knowledge of literature: it is the knowledge of life, from life. This English translation will be of great interest to English-speaking scholars in the fields of Global and Area Studies, Literary Studies, Cultural Studies, History, Political Science, and many more."--